The influence of morality on Dostoievski’s novel: Crime and punishment - Angeles Baca, Jesús Roberto (2024)
This analysis of Fyodor Dostoevsky's work, Crime and Punishment, deeply explores 3 aspects related to morality that is witnessed in the protagonist Raskolnikov. The first aspect is about the moral dilemma that Rodion has before and after committing the crime. The second is how their Christian morality influences their thoughts and actions. And the third aspect is about how our morality can manifest itself as an unconscious feeling of guilt through physical and psychological discomfort.